Persepsi ibu balita terhadap vaksinasi MR di wilayah kerja Puskesmas Beji: alasan penolakan dan penerimaan - Lia Arsyina; Ayu Amalia Rahmi; Ayudhia Rachmawati; Dortua Lince Sidabalok; Nada Amirah; Redi Yudha Irianto; Evi Martha; Bambang Wispriyono (Berita Kedokteran Masyarakat (BKM), 2019)
Maternal perceptions of MR vaccination in work area of Puskesmas Beji: explanations of reasons for and againts Purpose: Data from the Ministry of Health shows that as of October 2018, the coverage of MR vaccination nationally still has not reached the target. Depok is one of the cities that has not reached the target. This is due to the rejection of the child's parents. Therefore, the purpose of this study was to find out how the mother's perception and find out the reasons for acceptance and rejection of MR vaccination. Method: This research is a qualitative study with 23 informants consisting of mothers of children under five (mothers agree and disagree), cadres, midwives, and heads of Puskesmas uses Focus Group Discusion and In-depth Interview. Results: The results of this study found that for knowledge, mothers who agreed were mostly know about MR vaccination, while most mothers who did not agree admitted that they did not know. Whereas for perceptions, most of the mothers who disagree have a negative perception of MR vaccination, while most mothers who agree have positive perceptions of MR vaccination. There are also various reasons why mothers accept or refuse MR vaccination. Conclusion: Mother's perception of MR vaccination is one of the causes of rejection, resulting in MR vaccination coverage in Depok not yet reaching the national target.